Evaluation of weather radar rainfall estimation for nowcasting - Bacelar, Luiz Carlos Salgueiro Donato (2018)
This article presents the first evaluation of the method used by the Brazilian Centre for Monitoring and Early Warning of Natural Disasters for the short term forecast (nowcasting) of precipitation by weather radar. In this evaluation, four cases of intense rainfall in the radius of Pico do Couto radar were studied, giving the flood risk alerts sent for the municipality of Nova Friburgo, in the state of Rio de Janeiro. In relation to rain gauge data, a median under rate of 43% for the radar precipitation was observed when using the SRI (Surface Rainfall Intensity) method. After the rainfall correction, the cross-correlation extrapolation method was evaluated for the 30, 60, 90 and 120 minute forecast horizons, with accumulated precipitation every 30 minutes. The probabilities of detection (POD) obtained higher values for lower rainfall thresholds (at least 1 or 5 mm of accumulated rainfall) when compared to larger amount accumulated (20 and 30 mm). The spatial and temporal series of rainfall presented higher errors (MAE and RMSE) for 90 and 120 minutes of forecast. For all the events, an overestimate (PBIAS positive) of the predictions was observed in relation to the observed radar rain field itself.